NLTE modelling of integrated light spectra: abundances of barium, magnesium, and manganese in a metal-poor globular cluster - Eitner, Philip; Bergemann, Maria; Larsen, Søren (Astronomy and astrophysics, 2019)
Aims: We study the effects of non-local thermodynamic equilibrium ( NLTE) on the abundance analysis of barium, magnesium, and manganese from integrated light spectroscopy, as typically applied to the analysis of extra-galactic star clusters and galaxies. In this paper, our reference object is a synthetic simple stellar population ( SSP) representing a mono-metallic alpha-enhanced globular cluster with the metallicity [Fe/H] = 2.0 and the age of 11 Gyr. Methods. We used the MULTI2.3 program to compute LTE and NLTE equivalent widths of spectral lines of Mg I, Mn I, and Ba II ions, which are commonly used in abundance analyses of extra-galactic stellar populations. We used ATLAS12 model atmospheres for stellar parameters sampled from a model isochrone to represent individual stars in the model SSP. The NLTE and LTE equivalent widths calculated for the individual stars were combined to calculate the SSP NLTE corrections. Results. We find that the NLTE abundance corrections for the integrated light spectra of the metal-poor globular cluster are significant in many cases, and often exceed 0.1 dex. In particular, LTE abundances of Mn are consistently under-estimated by 0 : 3 dex for all optical lines of Mn I studied in this work. On the other hand, Ba II, and Mg I lines show a strong differential effect: the NLTE abundance corrections for the individual stars and integrated light spectra are close to zero for the low-excitation lines, but they amount to -0.15 dex for the strong high-excitation lines. Our results emphasise the need to take NLTE effects into account in the analysis of spectra of individual stars and integrated light spectra of stellar populations.
Gesehen am 05.09.2019